THE EFFECTIVENESS OF COLLABORATIVE STRATEGIC READING (CSR) IN IMPROVING STUDENTS' READING COMPREHENSION IN NARRATIVE TEXT - Primula, Denissa Femi (2016)
This research was aimed to examine the effectiveness of CSR as reading strategies to improve students' reading comprehension and to find out the students' responses toward CSR. The participants of the study was one class of eighth grade of Junior High Schools in Bandung consist of 33 students. The research method used was quasi-experimental with one group pretest-posttest design to collect the data. The data of the study were gathered through pretest, posttest, and questionnaire. The data from pretest and posttest were analyzed by using dependent test. Meanwhile, the questionnaire were analyzed by using Likert scale. The findings from dependent t-test showed that there were significant difference between pretest mean and posttest mean. It means, there were improvement in student's reading comprehension. The improvement includes vocabulary and knowledge enhancement, and reading comprehension skill, such as read to get information, read to organize, and read to evaluate. However, the result of gain index showed that the improvement of experimental group (g=0.12) was low. Thus, it can be conclude that CSR is low effective to increase students' reading comprehension. Moreover, the findings from the questionnaire showed the positive and the negative response toward CSR. The positive responses of CSR include helping students understand the text easily, getting the students involved in learning activity, and helping them to improve English ability. The negative responses of CSR include CSR made the students bored since they had to read based on the steps of CSR and it is considered as complicated strategy.;--- Penelitian ini bertujuan untuk menguji efektivitas CSR sebagai strategi membaca untuk meningkatkan pemahaman membaca siswa dan untuk menemukan respon siswa terhadap CSR. Partisipan dalam penelitan ini adalah siswa kelas VIII SMP yang terdiri dari 33 orang siswa. Untuk mengumpulkan data, metode penelitian yang digunakan adalah quasi-experimental dengan desain penelitian One Group Pretest-Posttest Design. Data dalam penelitian ini dikumpulkan dengan menggunakan pretest, posttest, dan angket. Data yang didapat dari pretest dan posttest dianalisis menggunakan dependent test. Sedangkan data angket dianalisis menggunakan skala Likert. Penemuan dari dependent test menunjukkan bahwa terdapan perbedaan yang signifikan antara rataan pretest dan rataan posttest. Artinya, ada peningkatan pada pemahaman membaca siswa. Peningkatan tersebut dari segi kosakata, pengetahuan, dan kemampuan pemahaman membaca, misalnya membaca untuk mendapatkan informasi, membaca untuk mengatur, membaca untuk mengevauasi. Namun, hasil dari indeks gain menunjukkan bahwa peningkatan tersebut terkategori rendah (g=0.12). Oleh karena itu, dapat disimpulkan bahwa efektivitas CSR dalam meningkatkan pemahaman membaca siswa rendah. Selain itu, penemuan dari angket menunjukkan positif dan negative respon terhadap CSR. Respon postitif terhadap CSR meliputi: membantu siswa memahami teks lebih mudah, membuat siswa terlibat dalam kegiatan pembelajaran, dan membantu siswa meningkatkan kemampuan Bahasa Inggris. Respon negative terhadap CSR meliputi: CSR membuat siswa bosan karena mereka harus membaca berdasarkan tahapan membaca CSR, dan CSR dianggap sebagai strategi yang rumit.